How do you solve by substitution 4x-9y=-21 and 4x+3y=-9?

1 Answer
Jun 8, 2015

(A): 4x-9y=-21
(B): 4x+3y=-9
We firstly obtain x or y from (A):
4x=9y-21

x=9/4y-21/4

And then we put this result at the place of x in (B).

4(x)+3y=-9 -> 4(9/4y-21/4)+3y=-9
9y-21+3y=-9
12y=12
y=1

It is not the end! Now that we found y we have to find x. We can basically substitute y=-5/2 in one of the two equations (for example (A) ).
4x-9(y)=-21 -> 4x-9(1)=-21
4x=-21+9=-12
x=-3

So the solution of the system is (x,y)=(-3,1)